Connecting the Internet of things : IoT connectivity standards and solutions - Kumar, Anil; Hussain, Jafer; Chun, Anthony (Apress, 2023)
Navigating the fragmented IoT connectivity ecosystem of standards, protocols, and architectures can be a challenge. Not to mention scaling a solution to a viable product. This book guides you through this fractured landscape with real world examples and projects that can be leverage for an IoT product. Backed by an overview of IoT use cases and key connectivity elements of IoT solutions, you'll gain an understanding of the breadth of the IoT landscape and the fragmentation of connectivity standards and solutions and the challenge in navigating the many standards and technologies. You'll also be able to understand the essentials of connectivity including, hardware, software, and business models. IoT is essential for increasing productivity of many industries and quality of life (making the world smart and autonomous). Both wired and wireless connectivity technologies are essential ingredients in an IoT product. Written by Intel engineers and architects, Connecting the Internet of Things understands that connectivity is a key topic of IoT and comprehensively covers the topic from a system engineering and practical perspective. You will: Understand the trade offs between different wireless technologies and network topologies Use wireless technologies in IoT products Examine connectivity technologies and considerations on selecting it for the IoT use cases Assemble all of the components of a working solution Scale your solution to a product Review emerging connectivity technologies for addressing new use cases Advance and optimize the performance of existing technologies.